A study on investor’s awareness in mutual fund as an investment option / Siti Aisyah Daud - Daud, Siti Aisyah (2013)
In Malaysia and throughout the world, Mutual Trust funds have experienced phenomenal growth in the past few years. This growth reflects the suitability of collective investments in Malaysia, as a means for the smaller investor to accumulate capital over the longer term. Researcher conducts this study to study investor’s awareness in mutual fund as an investment option. The independent variable that researcher been used was return potential, liquidity, transparency, and social influences. A 100 questionnaire was distributed to the respondent to know investor’s awareness in mutual fund as investment option. Researcher gives questionnaire to the staff in Kolej Universiti Islam Melaka as a sample in this study. The design of questionnaire is focus on likert scales to know the level of understanding how strongly agree or strongly disagree of the respondent with the statement regarding the principles. As a conclusion, this study gets the appropriate data to measure the level of investor’s awareness in mutual fund as investment option.